Effect of surface treatment of zirconia-ceramic dental restorations / Firas Abdulameer Farhan - Firas Abdulameer, Farhan (2018)
The zirconia-ceramic restoration (ZCR) is used as substitutes for the metal-ceramic restoration. Clinical studies of ZCRs showed a high fracture incidence of veneering layer than metal-ceramic restorations. This attributed to the low bond strength of zirconia to veneering ceramic as a result of lacking glass content in its matrix. Surface treatment was proposed to improve the bonding strength between zirconia and veneering ceramic. Several studies revealed that surface treatment such as airborne particle abrasion (APA) is responsible for generating chipping of veneering ceramic. The study aimed to develop a new zirconia coating to increase the bonding strength between zirconia substrate and veneering porcelain. Three groups of 150 zirconia specimens (discs, rods and crowns) were divided according to the type of surface treatments. Group M1, the unsintered zirconia specimens were coated with a mixture of glaze porcelain powder and partiallysintered zirconia powder prepared at 1100 °C. Group M2 was coated with a mixture of ceramic liner paste and partially-sintered zirconia powder. The APA group (control), the sintered zirconia specimens were abraded with 50 µm aluminium oxide powder. Group M1 and M2 were further subdivided according to partially sintered zirconia powder with two selected particle sizes, A (26 ± 0.3 µm) and size B (47 ± 0.5 µm) into M1A, M1B, M2A and M2B respectively. Surface area roughness (Sa) was measured by surface texture analyser. Surface morphology and elemental composition were analysed by scanning electron microscope (SEM). Crystallographic phases were identified by X-ray diffraction (XRD). The coefficient of thermal expansion (CTE) was assessed with a thermomechanical analyser. Shear bond strength (SBS) test was evaluated by a universal testing machine (UTM). Fracture strength (FS) test prepared by Cercon CAD/CAM system and measured with UTM. Fractographic analysis of SBS and FS were examined iv by a stereomicroscope and SEM, where for each test and measurement, 10 specimens were used per group. Finite element analysis (FEA) was simulated and predicted the stress distributions of the static oblique load in coated and non-coated zirconia crown models. The collected data were analysed by one-way ANOVA and Tukey HSD test at (P<0.05). Surface roughness results showed significant differences among all groups (P<0.000). The M1B group exhibited a higher Sa value (10.33 ± 0.59 µm) among the tested groups. XRD analysis showed tetragonal and monoclinic phases in the control group while only tetragonal was detected in the coated groups. The SBS of the coated groups were higher than those of the control group. The M1B group showed significantly higher SBS (37.54 ± 4.38 MPa) compared to other tested groups (P<0.05). The FS of the coated M1B group (647.92 ± 97.33 N) had higher FS compared to other groups (P<0.00). FEA showed the coated crown models have lower stress level than the non-coated model. The new coating (M1B) by airbrush spray technique can be considered as an alternative method to APA treatment to improve the bond strength of zirconia substrate to veneering ceramic. It is an applicable surface treatment for improving the clinical performance of the coated ZCR.